Power through 'us': leaders' use of we-referencing language predicts election victory. - Niklas K Steffens (Public Library of Science (PLoS), 2013)
Leaders have been observed to use distinct rhetorical strategies, but it is unclear to what extent such strategies are effective. To address this issue we analyzed the official election campaign speeches of successful and unsuccessful Prime Ministerial candidates in all 43 Australian Federal elections since independence from Britain in 1901 and measured candidates' use of personal ('I', 'me') and collective pronouns ('we', 'us'). Victors used more collective pronouns than their unsuccessful opponents in 80% of all elections. Across all elections, victors made 61% more references to 'we' and 'us' and used these once every 79 words (vs. every 136 words for losers). Extending social identity theorizing, this research suggests that electoral endorsement is associated with leaders' capacity to engage with, and speak on behalf of, a collective identity that is shared with followers whose support and energies they seek to mobilize.